Comparison between PI and PR Current Controllers of a Grid- Connected Photovoltaic System Under Load Variation - Soukaina Essaghir; Mohamed Benchagra; Noureddine El barbri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents a current control technique for a three-phase grid-connected DC /AC inverter which is used in photovoltaic systems. A Proportional-Resonant (PR) controller is used for replacing the conventional Proportional-Integral (PI) controller in this system. By comparison with the conventional PI control method, the PR control can introduce an infinite gain at the fundamental frequency and hence can achieve zero steady-state error. The proposed model is based on two control loops: the first control loop regulates DC link voltage and the second one is used to keep the injected current to the grid in phase with the voltage by means of a Phase Locked Loop (PLL) in order to achieve a unit power factor and to adjust the output power as required. In order to examine the effectiveness of the suggested control, a simulation using the Matlab/Simulink software has been done and it’s concluded from the simulation results that the presented control by using the PR controller can be able to maintain maximum active power and to keep always a unity power factor despite variation load.